SmartCrowd: novel approach to big crowd management using mobile cloud computing - Ali, Mohammed Fazil; Bashar, Abul; Shah, Asadullah (IEEE, 2015)
This paper presents a novel approach, Smartcrowd, utilizing the mobile Cloud Computing (MCC) as a platform to find a solution to manage a large human crowd. The proposed solution caters to big crowd management on important Islamic pilgrimages of Hajj and Umrah in the cities of Makkah and Madinah in Saudi Arabia during a fixed time every year. In recent years MCC has achieved a very important status in all walks of human life for various services, including instant file sharing, online storage facilities, Voice over Internet Protocol (VoIP) calling, Instant messaging and Social Networking. We discuss current challenges and issues in implementation of MCC to achieve desired targets, such as cloud accessing issues, Mobile routing standard analysis and mobile application. As a continuation of this research it is planned to survey the pilgrim experiences and compile suggestions for incorporating additional features in our proposed solution.